2021
DOI: 10.3390/cancers13205086
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Signaling in the Pancreatic Tumor Microenvironment

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is associated with poor clinical outcomes, largely attributed to incomplete responses to standard therapeutic approaches. Recently, selective inhibitors of the Transforming Growth Factor β (TGFβ) signaling pathway have shown early promise in the treatment of PDAC, particularly as a means of augmenting responses to chemo- and immunotherapies. However, TGFβ is a potent and pleiotropic cytokine with several seemingly paradoxical roles within the pancreatic tumor microenviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 173 publications
(208 reference statements)
0
32
0
Order By: Relevance
“…Accordingly, TGFb pathway inhibition is showing early promise in clinical trial for PDAC patients, particularly when combined with chemo- (32) or immunotherapy (33). While related trials are ongoing (34), to our knowledge, no studies have examined whether patients with genetic defects in the TGFb/SMAD4 signaling pathway will have alterations in local immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, TGFb pathway inhibition is showing early promise in clinical trial for PDAC patients, particularly when combined with chemo- (32) or immunotherapy (33). While related trials are ongoing (34), to our knowledge, no studies have examined whether patients with genetic defects in the TGFb/SMAD4 signaling pathway will have alterations in local immune function.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our KEGG enrichment analysis showed that the TGF-β signaling pathway was only activated in HPNE cells in response to ROS stress, while the mRNA transcripts associated with the Jak/STAT signaling pathway were mainly seen in PANC-1 cells after H 2 O 2 treatment. As a double-edged sword, the TGF-β signaling pathway can suppress tumor development by inhibiting cell proliferation and inducing apoptosis, but it can also promote cancer cell invasion and metastasis [31][32][33]. The Jak/STAT pathway is activated in many solid tumor cells and contributes to the malignant properties of cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, selective inhibitors of the TGF-β signaling pathway are now under evaluation, showing early promise. However, the paradoxical role this growth factor may play in the tumor microenvironment, for example in the case of pancreatic adenocarcinoma, has led to questions regarding the potential biological consequences of inactivating selected components from this pathway, to identify the most effective combination therapy (Principe et al, 2021).…”
Section: Tgf-βmentioning
confidence: 99%